A systematic exploration reveals the potential of spermidine for hypopigmentation treatment through the stabilization of melanogenesis-associated proteins - Brito, Sofia; Heo, Hyojin; Cha, Byungsun; Lee, Su Hyun; Chae, Sehyun; Lee, Mi Gi; Kwak, Byeong Mun; Bin, Bum Ho (Scientific Reports, 2022)
Spermidine (SPD), a polyamine naturally present in living organisms, is known to prolong the lifespan of animals. In this study, the role of SPD in melanogenesis was investigated, showing potential as a pigmenting agent. SPD treatment increased melanin production in melanocytes in a dose dependent manner. Computational analysis with RNA-sequencing data revealed the alteration of protein degradation by SPD treatment without changes in the expressions of melanogenesis-related genes. Indeed, SPD treatment significantly increased the stabilities of tyrosinase-related protein (TRP)-1 and -2 while inhibiting ubiquitination, which was confirmed by treatment of proteasome inhibitor MG132. Inhibition of protein synthesis by cycloheximide (CHX) showed that SPD treatment increased the resistance of TRP-1 and TRP-2 to protein degradation. To identify the proteins involved in SPD transportation in melanocytes, the expression of several solute carrier (SLC) membrane transporters was assessed and, among 27 transporter genes, SLC3A2, SLC7A1, SLC18B1, and SLC22A18 were highly expressed, implying they are putative SPD transporters in melanocytes. Furthermore, SLC7A1 and SLC22A18 were downregulated by SPD treatment, indicating their active involvement in polyamine homeostasis. Finally, we applied SPD to a human skin equivalent and observed elevated melanin production. Our results identify SPD as a potential natural product to alleviate hypopigmentation.
Keywords: Animals; Humans; Hypopigmentation; Melanins; Melanocytes; Polyamines; Spermidine